Impact of role-play on improving tenth-grade students’ English-speaking skills and enhancing their personality skills - Raba, Ahmed Awad; Itmeizeh, Mahmoud; Jawabreh, Tasnim (International Journal of Innovative Research and Scientific Studies, 2025)
This research aimed to examine the impact of role-play on improving students' speaking skills and personality skills. To this end, four academic sections comprising 50 male and female students from the tenth grade were selected: two sections for males and another two sections for females from Haley International School in Al-Khobar city in Saudi Arabia. The four sections were distributed into two groups: the experimental group and the control group. Results showed that the experimental group, which received instructions through the role-playing strategy, had significantly higher scores in the post-test of speaking skills and personality skills compared to the control group, which received traditional instruction. This suggests that role-play is effective in improving both speaking and personality skills in language learners. Interestingly, there was no statistically significant difference in students’ scores due to gender, indicating that role-play is equally effective for both male and female students. These findings have important implications for language teachers who are looking for innovative and engaging ways to improve their students' language skills. By incorporating role-play activities into their lessons, teachers can help their students develop not only their language proficiency but also their personality skills.